Determination of Polar Compounds in Guava Leaves Infusions and Ultrasound Aqueous Extract by HPLC-ESI-MS - Elixabet Díaz-de-Cerio; Vito Verardo; Ana María Gómez-Caravaca; Alberto Fernández-Gutiérrez; Antonio Segura-Carretero (Journal of Chemistry)
Literature lacks publications about polar compounds content in infusion or guava leaves tea. Because of that, a comparison between different times of infusion and a conventional ultrasound aqueous extract was carried out. Several polar compounds have been identified by HPLC-ESI-MS and their antioxidant activity was evaluated by FRAP and ABTS assays. Four different classes of phenolic compounds (gallic and ellagic acid derivatives, flavonols, flavanones, and flavan-3-ols) and some benzophenones were determined. The quantification results reported that the order, in terms of concentration of the classes of polar compounds in all samples, was flavonols > flavan-3-ols > gallic and ellagic acid derivatives > benzophenones > flavanones. As expected, the aqueous extract obtained by sonication showed the highest content in the compounds studied. Significative differences were noticed about the different times of infusion and five minutes was the optimal time to obtain the highest content in polar compounds using this culinary method. All the identified compounds, except HHDP isomers and naringenin, were positively correlated with antioxidant activity.